Gait analysis in patients undergoing ACL reconstruction according toKenneth Jones’ technique - Bacchini, M.; Cademartiri, C.; Soncini, G. (Acta Biomedica Atenei Parmensis, 2009)
The anterior cruciate ligament is essential for knee stability, and its injury, both acute and in the case of chronic knee instability, promotes meniscal degenerative alterations, as well as the onset and progression of gonarthrosis. In this retrospective study,  young adults engaged in nonprofessional sportive activities undergoing ACL reconstruction by the Kenneth-Jones technique were assessed clinically and with gait analysis, to detect any deficits persisting even after rehabilitation at a follow- up of approximately 6 months. Eight patients who had undergone elective ligament reconstruction by Kenneth-Jones were assessed between the 5th and 7th month postsurgery with clinical-anamnestic investigation, including the Hughston Clinic subjective knee questionnaire and by gait analysis with the EL.I.Te. system. Gait analysis showed a reduction of ACL protection mechanisms during initial stance; furthermore, the operated limb globally exhibited greater difficulty in muscle recruitment. Residual deficits in muscle recruitment, exposing the reconstructed ligament to possible injuries, persist after a rehabilitation program and after resuming of pre-surgery activities, thus adjustment of the rehabilitative program on the basis of these findings is recommended.